A green Lewis development model. (6th March 2020) - de Oliveira, Guilherme; Lima, Gilberto Tadeu
Abstract: This paper develops an environmental extension of a Lewis dual economy model, in which the interaction between environmental quality and economic growth, in one of its several dimensions, is explicitly modeled to explore long‐run effects of a pollution abatement rule in developing economies. The government requires the modern sector to dedicate a fraction of its output to pollution abatement, with such profitability‐reducing fraction being endogenous to the level of environmental quality. Meanwhile, the level of environmental quality positively affects labor productivity, profits and, therefore, savings, which has a positive impact on capital accumulation. It is shown that this pollution abatement requirement, by affecting profitability in the modern sector both negatively and positively, makes for the emergence of an ecological development trap from which a developing dual economy, if left to the free play of its structural forces, never escapes. Fortunately, however, this economy can be released from such a trap not only through a standard Big Push, in the spirit of Rosenstein‐Rodan, but also by means of what we call an Environmental Big Push.